A Black Cat in Cortazar´s Works: Comparison Between Julio Cortázar and Edgar Allan Poe - Alonso Menchero, Guillermo (Journal of Artistic Creation and Literary Research, 2025)
Edgar Allan Poe is considered by many critics as one of the most known figures of the first half of the nineteenth century. A purely romantic man and closely linked to his European contemporaries. The influence of his works has been found in many authors after his death, becoming part of today’s existing cultural canon. Therefore, this essay will seek not only to perform an analysis of the unreliable narrator in Poe’s work, but also to search and make a comparison with the Argentine writer Julio Cortázar, who was not only a Poe translator, but also a big fan of him. The work of Julio Cortázar will be framed within a Gothic perspective in addition to fitting some of his works under the same point of view as Poe’s unreliable narrator, trying to find the influence of Edgar Allan Poe in the stories of Julio Cortázar without making a one-to-one comparison between both of them.